Congenital true leukonychia totalis - Vyshak, B. M.; Lunge, Snehal B. (International Journal of Research in Dermatology, 2020)
Congenital true leukonychia totalis is very rare hereditary condition characterized by milky white discoloration of all nails. It has mainly autosomal dominant mode of inheritance and autosomal recessive in few cases. It may be inherited or associated with systemic disease or idiopathic. It has been linked to the mutations in PLCD1 gene on chromosome 3p21.3-p22. Leukonychia totalis is associated with multiple systemic diseases such as congenital hyperparathyroidism, Hodgkin's lymphoma, Leopard syndrome, Epiphyseal dysplasia syndrome, Bart Pumphrey syndrome etc. we report a case of sporadic congenital leukonychia totalis in a 24 years female without any systemic abnormalities.